Trends in private investment in developing countries 1994 : statistics for 1970-92 - Miller, Robert R (World Bank WashingtonUS, 1994)
Provides private and public investment data. Includes aggregate data on net foreign direct investment and a discussion on the effects of recent privatization activities on private investment flows.